Penentuan Cadangan PreminTahunan Retrospektif AsuransinJiwa Dwiguna Kasus JointnLife dengannMenggunakan Metode Fackler - Noni Aryanti; Defri Ahmad (Journal of Mathematics UNP, 2020)
Abstract –The problem that insurance companies often face is that their small reserve premiums are acquired. The reserves will be used to pay compensation to insurance participants when a claim is made. As a effect, insurance companies will suffer losses. Therefore, it is discussed the determination of annual premium reserves of endowment insurance for joint life cases using the Fackler method with retrospective reserve. The Fackler method is used to calculate net premium reserves in the next few years in sequence. The calculationnof the reservenofnendowment insurance isndonenby forming a combined mortality table, determining the combined life annuity, a single premium, and an annual net premium. By using such calculation, the annual net premium formula and retrospective annual net premium reserve formulation are obtained. Keywords—premium reserves, retrospective, endowment insurance, joint life, Fackler method